Intrasurgical Protein Layer on Titanium Arthroplasty Explants: From the Big Twelve to the Implant Proteome. Issue 2 (28th February 2019) - Jäger, Marcus; Jennissen, Herbert P.; Haversath, Marcel; Busch, André; Grupp, Thomas; Sowislok, Andrea; Herten, Monika
Abstract : Purpose: Aseptic loosening in total joint replacement due to insufficient osteointegration is an unsolved problem in orthopaedics. The purpose of the study is to obtain a picture of the initial protein adsorption layer on femoral endoprosthetic surfaces as the key to the initiation of osseointegration. Experimental design: The paper describes the first study of femoral stem explants from patients for proteome analysis of the primary protein layer. After 2 min in situ, the stems are explanted and frozen in liquid nitrogen. Proteins are eluted under reducing conditions and analyzed by LC‐MS/MS. Results: After exclusion of proteins identified by a single peptide, the implant proteome is found to consist of 2802 unique proteins. Of these, 77% are of intracellular origin, 9% are derived from the plasma proteome, 8% from the bone proteome, and four proteins with highest specificity score could be assigned to the bone marrow proteome (transcriptome). The most abundant protein in the adsorbed total protein layer is hemoglobin (8–11%) followed by serum albumin (3.6–6%). Conclusions: A detailed knowledge of the initial protein film deposited onto the implants, as demonstrated here for the first time, may help to understand and predict the response of the osseous microenvironment to implant surfaces.